Efficient Photoinduced Electron Transfer from Pyrene‐o‐Carborane Heterojunction to Selenoviologen for Enhanced Photocatalytic Hydrogen Evolution and Reduction of Alkynes. Issue 5 (26th December 2021) - Yang, Xiaodong; Zhang, Bingjie; Gao, Yujing; Liu, Chenjing; Li, Guoping; Rao, Bin; Chu, Dake; Yan, Ni; Zhang, Mingming; He, Gang
Abstract: A series of pyrene or pyrene‐ o ‐carborane‐appendant selenoviologens (Py‐SeV 2+, Py‐Cb‐SeV 2+ ) for enhanced photocatalytic hydrogen evolution reaction (HER) and reduction of alkynes is reported. The efficient photoinduced electron transfer (PET) from electron‐rich pyrene‐ o ‐carborane heterojunction (Py‐Cb) with intramolecular charge transfer (ICT) characteristic to electron‐deficient selenoviologen (SeV 2+ ) ( k ET = 1.2 × 10 10 s −1 ) endows the accelerating the generation of selenoviologen radical cation (SeV + ) compared with Py‐SeV 2+ and other derivatives. The electrochromic/electrofluorochromic devices' (ECD and EFCD) measurements and supramolecular assembly/disassembly processes of SeV 2+ and cucurbit[8]uril (CB[8]) results show that the PET process can be finely tuned by electrochemical and host–guest chemistry methods. By combination with Pt‐NPs catalyst, the Py‐Cb‐SeV 2+ ‐based system shows high‐efficiency visible‐light‐driven HER and highly selective phenylacetylene reduction due to the efficient PET process. Abstract : A series of pyrene or pyrene‐ o ‐carborane‐appendant selenoviologens (Py‐SeV 2+, Py‐Cb‐SeV 2+ ) are successfully synthesized. The intramolecular electron transfer (ICT) of Py‐Cb strongly enhances the PET from the donor to electron‐deficient SeV 2+, which accelerates the formation of selenoviologen radical cations (SeV + ) efficiently, enabling enhanced visible‐light‐driven HER and highly selective phenylacetylene reduction.